Understanding Current Staff Experiences, Practices and Needs in Supporting Young People with Neurodevelopmental Disorders in the Queensland Youth Justice System. Issue 4 (8th September 2022) - Heanue, Alanna; Gullo, Matthew J.; Hayes, Nicole; Passmore, Hayley; Reid, Natasha
Abstract: Young people with neurodevelopmental disorders are overrepresented in the youth justice system and face many disadvantages due to their impairments. The current study investigated what factors predict and contribute to the behavior of youth justice professionals working in the Queensland (QLD) youth justice system, utilizing a behavior change wheel framework. Eighty-one youth justice professionals participated in an online survey assessing capability, opportunity and motivation and additional open-ended questions capturing their recommendations for improvement. Results demonstrated that training frequency, capability, opportunity and motivation significantly predicted behaviors to identify and support young people with neurodevelopmental disorders (i.e., target behaviors). Capability ( p = <.001) and motivation ( p = .02) were significant independent predictors of the target behaviors. Examination of open-ended responses provided by the youth justice professionals identified several key areas, consistent with existing literature, which were in need of modifications to further support young people with neurodevelopmental disorders. These included: use of language, availability of resources, increased liaison with stakeholders, and knowledge and understanding of neurodevelopmental disorders. Overall, the current results provide helpful directions in terms of future targets for implementation strategies and interventions to better support young people with neurodevelopmental conditions who are involved with the QLD youth justice system.